A portable three-component displacement measurement technique using an unmanned aerial vehicle (UAV) and computer vision: A proof of concept. (May 2021) - Perry, Brandon J.; Guo, Yanlin
Abstract: This study proposes a new remote sensing technique to measure three-component (3C) dynamic displacement of three-dimensional (3D) structures. A sensing system with a UAV platform and contact-free sensors (e.g., optical and infrared (IR) cameras) is employed to provide a portable and convenient alternative to conventional approaches that require sensor installation on a structure. The original contributions of this study include (1) integrating both optical and IR cameras with a UAV platform to measure dynamic structural response, and (2) developing new data post-processing algorithms (based on target identification, Direct Linear Transformation, and active stereo vision) to simultaneously extract the 3C displacement of a 3D structure from optical and IR videos, which presents a unique advantage compared to the existing UAV-based displacement measurement techniques that allow the measurements in only one or two directions using optical cameras or laser sensors. The efficacy of the proposed technique is validated through laboratory experiments. Graphical abstract: Highlights: 3D dynamic displacements are measured simultaneously. Optical/infrared sensors and a UAV are integrated to a portable sensing system. Algorithms using active stereo vision are developed to measure depth displacement. High measurement accuracy is achieved with a fast-computational speed.